RECONSTRUCTION OF THE WASTE MANAGEMENT LAW BASED ON WELFARE VALUE - M. Hasyim Muallim; Gunarto Gunarto; Anis Mashdurohatun (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
To achieve the condition of society who live healthy and prosperous in the future, it will be necessary to have a healthy living environment. From the aspect of waste management, the healthy word would mean a condition that would be achieved if the waste can be managed well so that the living environment where human activity there will be clean (Permen PU number: 21 / PRT / M / 2006). Vision of the development of waste management systems of Departemen Pekerjaan Umum dan Perumahan is " Permukiman Sehat Yang Bersih Dari Sampah", it is reflects to achieve of a good condition and healthy environment. In general, according to the Peraturan Menteri PU nomor: 21/PRT/M/2006, the areas that get solid waste services will either be shown to have the following conditions: a.) The society has access to handle the waste that are producted from daily activities, either in living environment, commerce, offices, and other public places, b). The society has a clean living environment because the waste that are produced can be handled properly. c). The society are able to maintain their health because there is no waste that could potentially be material transmission of diseases such as diarrhea, typhoid, dysentery, and others; and environmental disturbances from pollution of air, water or soil. d.) The sociaty and the business / private sector have the opportunity to participate in waste management so as to obtain benefits for welfare. Until now, waste management paradigm used is: GATHERING-TAKING and REMOVING, and the mainstay of a city in resolving problems of waste is landfilling in TPA. The city manager is less likely to give serious attention to the TPA, so came the failure cases of TPA. The city manager seems to assume that their TPA can solve all waste problems, without having to give proportionate attention to these facilities. TPA can be time bomb for the city manager. To achieve optimal waste services, it's time for a paradigm change municipal waste management. Transformative paradigm is the concept of municipal waste management to prevent or minimize the generation of pollution and other negative impacts that are detrimental to society and the environment. According to Witoelar (2006: 2) takes pioneers to change the paradigm of waste management from the approach end of the pipe (end of pipes) that dispose of waste directly to TPA towards waste management with the principles of 3R is Reduce, Reuse and Recycle. In the case of this paradigm change is far behind the other countries. For example, according to Buclet and Olivier waste management paradigm change in most European countries has been started since 1970. The waste management policy emphasis on waste reduction at source, sorting and recycling. A very important starting point in this paradigm change is a change of policy toward the minimization of garbage at the source, rather than on disposal. According to Law No.18 of 2008 on Waste Management, there are two main groups of waste management are: a.) Reduction of waste (waste minimization) consisting of restrictions on the trash, reuse, and recycling, b) Waste management (waste handling ). This condition is emphasized that the main priorities that should be done by all parties is how to reduce waste as much as possible. Part of waste or residue from waste reduction activities remaining is then performed processing (treatment) and heaping (landrilling). Waste management is an important issue in the problems of city environment that is faced in line with population growth and an increase in construction activity. The increase in waste volume grows exponentially which has not been accompanied by an increase in local government revenue equivalent to the management of municipal solid waste (Puslitbang Permukiman, Bandung 2014). This relates to the increasingly difficult and expensive to get the location of the final disposal (TPA), also are located farther away has extended transport and increase the cost of transportation.